KAPASITAS AEROBIK MAHASISWA PEMAIN WUSHU LEBIH BAIK DARIPADA MAHASISWA BUKAN PEMAIN WUSHU DI UNIVERSITAS UDAYANA - Bhyantari, Ni Putu Ruspata; Muliarta, I Made (E-Jurnal Medika Udayana; Vol 5 No 5 (2016): E-jurnal medika udayana, 2016)
Sport wushu requires a good aerobic capacity. The indicator used to measure aerobic capacity is the maximum oxygen capacity (VO2 max). The higher the VO2 max value, the better the aerobic capacity of individuals. VO2 max can be improved through regular physical exercise. The objective of this study was to compare the aerobic capacity based on indirect VO2 max among wushu player students and non-wushu player students in Udayana University. This study used analytical and cross sectional approach. 30 samples were chosen by purposive sampling consisted of 15 wushu player students and 15 non-wushu player students. Aerobic capacity was assessed using an indicator of indirect VO2 max measured by 2.4 km Cooper Test. The mean age of wushu player group and non-wushu player group were 21.00 ± 1.069 years and 20.73 ± 0.704 years. The mean VO2 max were 41.718 ± 2.1452 ml/kg/minute and 33.745 ± 2.4073 ml/kg/minute. The mean VO2 max of wushu player group was greater by 19.11% than non-wushu player group. 95% confidence interval with a lower limit of 6.2668 and upper limit of 9.6776. Independent t-test showed significant difference (p = 0.000) of aerobic capacity between wushu player group and non-wushu group. It can be concluded that aerobic capacity among wushu player students is better than non-wushu player students in udayana university.
Keywords: aerobic capacity, VO2 max, wushu player, non-wushu player, 2.4 km Cooper Test